Infliximab in inflammatory bowel disease: clinical outcome in a population based cohort from Stockholm County. Issue 6 (11th May 2004) - Ljung, T; Karlén, P; Schmidt, D; Hellström, P M; Lapidus, A; Janczewska, I; Sjöqvist, U; Löfberg, R
Abstract : Background: Several placebo controlled studies have demonstrated the efficacy of infliximab in inflammatory bowel disease (IBD) but the potential toxicity of this new biological compound has been less studied. Aim: To assess the use of infliximab in IBD in a population based cohort, with special emphasis on the occurrence of severe adverse events and mortality. Patients: All patients with IBD treated with infliximab between 1999 and 2001 in Stockholm County were evaluated. Methods: Prospective registration of clinical data was carried out. Retrospective analyses were made of possible adverse events occurring in relation to infliximab treatment. Adverse events requiring pharmacological treatment or hospitalisation were defined as severe. Clinical response was assessed as remission, response, or failure. Results: A cohort comprising 217 patients was assembled: 191 patients had Crohn's disease (CD), and infliximab was used off label for ulcerative colitis (UC) in 22 patients. Four patients were treated for indeterminate colitis (IC). Mean age was 37.6 (0.9) years (range 8–79). The mean number of infliximab infusions was 2.6 (0.1) (range 1–11). Forty two severe adverse events were registered in 41 patients (CD, n = 35). Eleven of the severe adverse events occurred postoperatively (CD, n = 6). Three patients with CD developed lymphoma (of which two were fatal), opportunistic infections occurred in two patients (one with UC, fatal), and two patients with severe attacks of IBD died due to sepsis (one with CD, one postoperatively with UC). One additional patient with UC died from pulmonary embolism after colectomy. Mean age in the group with fatal outcome was 62.7 years (range 25–79). The overall response rate was 75% and did not differ between the patient groups. Conclusions: Infliximab was efficacious as an anti-inflammatory treatment when assessed in a population based cohort of patients with IBD. However, there appear to be a significant risk of deleterious and fatal adverse events, particularly in elderly patients with severe attacks of IBD. Off label use of infliximab in UC and IC should be avoided until efficacy is proven in randomised controlled trials. The underlying risk of developing malignancies among patients with severe or chronically active CD in need of infliximab treatment is not known but the finding of a 1.5% annual incidence of lymphoma emphasises the need for vigilant surveillance with respect to this malignant complication.